Superconductivity emerging from a stripe charge order in IrTe2 nanoflakes - Sungyu Park (Nature Portfolio, 2021)
Superconductivity often appears due to suppression of competing electronic orders. Here, the authors present a contrary example showing a superconducting dome inside the parent phase with a stripe charge order in IrTe2 nanoflakes and identify their unusual superconducting properties.